Ethical and Sustainable Urban Tourism Development in Indonesia - I.B. Komang Surya Werdiyasa (Bali Tourism Journal, 2026)
Urban tourism has become an increasingly important driver of economic development, urban regeneration, and destination competitiveness in Indonesia. However, the rapid expansion of tourism in urban areas has also generated significant environmental, social, cultural, and governance challenges that question the long-term sustainability of tourism development. This study aims to examine the principles of ethical and sustainable urban tourism development in Indonesia by synthesizing contemporary perspectives on environmental ethics, social justice, community participation, and collaborative governance. The research employs a qualitative conceptual approach using a structured literature review and theoretical synthesis of scholarly publications concerning urban tourism, sustainable tourism, environmental responsibility, and tourism governance. Relevant literature published primarily between 2020 and 2026 was analyzed through thematic interpretation to identify recurring concepts and develop an integrated conceptual framework. The findings indicate that sustainable urban tourism should extend beyond conventional economic performance indicators and incorporate broader ethical considerations that prioritize environmental stewardship, social equity, cultural preservation, and residents' well-being. The analysis highlights that inadequate stakeholder participation, fragmented governance, and weak environmental management have contributed to challenges in Indonesian urban tourism, as illustrated by the experiences of Teras Cihampelas in Bandung and tourism development in Jakarta. The study further identifies four interconnected pillars of ethical urban tourism development: environmental responsibility, social equity, meaningful community participation, and responsible governance. These principles provide a comprehensive framework for evaluating tourism policies and guiding sustainable destination management. The study concludes that integrating ethical values into tourism planning can strengthen urban resilience, improve policy legitimacy, promote inclusive development, and ensure that tourism contributes to both community welfare and environmental sustainability. The proposed conceptual framework offers practical implications for policymakers, urban planners, and tourism stakeholders while providing a foundation for future empirical research on sustainable urban tourism in Indonesia.